The tribal placement of Urocorthylus Petrov, Mandelshtam & Beaver, with a description of the male of U. hirtellus Petrov et al., and notes on its biology (Coleoptera: Curculionidae: Scolytinae) - Johnson, Andrew J.; Sittichaya, Wisut; Lai, Shengchang; Li, You; Beaver, Roger A. (Zootaxa, 2023)
We show, using molecular data, that the enigmatic genus Urocorthylus Petrov, Mandelshtam & Beaver from Southeast Asia belongs in the scolytine tribe, Dryocoetini, and not in the almost wholly American tribe Corthylini, where it was originally placed. The male of Urocorthylus hirtellus Petrov, Mandelshtam & Beaver is described and figured for the first time, and new records from China are presented. Urocorthylus hirtellus is a bark beetle, and not an ambrosia beetle as originally hypothesised. Keys are provided to the genus within the Dryocoetini, and to the two species included in the genus.